A science didactic sequence based on inquiry-based teaching in the 9th year of Elementary School using Scratch - Strieder, Rosangela Lucia; Souza, Marcela Zoratti de; Hellmann, Miriam de Lima; Carvalho, José Wilson Pires (Seven Editora, 2024)
The research in question refers to an Investigative Didactic Sequence applied in the teaching of Science to students in the 9th year of Elementary School, as part of a master's thesis defended in the Stricto Sensu Postgraduate Program in Science and Mathematics Teaching - PPGECM , from the State University of Mato Grosso, UNEMAT/Barra do Bugres. The study aimed to understand the contributions of using Scratch Software in teaching the calculation of atomic mass to students in the 9th year of Elementary School and involved 13 students from a public school in the interior of the State of Mato Grosso. The science didactic sequence was developed over six meetings (14h), which consisted of stages of theoretical exploration of Chemistry concepts, followed by the use of Scratch Software to construct the Interactive Periodic Table, covering concepts of Chemistry, Mathematics and programming in block. During this interdisciplinary approach, students were able to understand and explore the properties of chemical elements, as well as calculate the atomic mass and at the end of the Didactic Sequence, a qualitative assessment of the results achieved was carried out, through observation and journaling. fieldwork, analysis of reports and questionnaires. The results highlighted the importance of interdisciplinarity in teaching, arousing students' interest through the construction of the Interactive Periodic Table in Scratch Software. This proved to be an effective pedagogical strategy to mediate the teaching of atomic mass calculation, contributing to the development of students' skills and improving the teaching process. DOI:https://doi.org/10.56238/sevened2024.009-015